2014
DOI: 10.1007/s12519-014-0526-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of chromosomal abnormalities in Sri Lankan children

Abstract: The prevalence of chromosomal abnormalities in Sri Lankan children undergoing cytogenetic analysis for suspected chromosomal disorders was relatively higher than that in Caucasian and other Asian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…46XY or 46XX, while karyotype abnormalities leading to sex chromosome DSD are less common. 14,15 Our study also showed similar results with only 1 case (1.9%) with a 45, X/46,XY mosaic karyotype.…”
Section: Discussionsupporting
confidence: 86%
“…46XY or 46XX, while karyotype abnormalities leading to sex chromosome DSD are less common. 14,15 Our study also showed similar results with only 1 case (1.9%) with a 45, X/46,XY mosaic karyotype.…”
Section: Discussionsupporting
confidence: 86%
“…A cytogenetic analysis of nearly 30,000 children with Down syndrome in England and Wales reported that 2.7% of the cases were due to Robertsonian translocations including rob(21q21q) [24]. A study conducted in our laboratories in 2015 showed a higher incidence (4.7%, 31/665) of Down syndrome due to Robertsonian translocations [25]. Herein, we expand the collection of cases to 91, of which majority were due to rob(14q21q) followed by rob(21q21q).…”
Section: Discussionmentioning
confidence: 99%
“…Although antenatal genetic testing for chromosomal abnormalities and other rare disorders are currently available, many children with these disorders are born because termination of pregnancies for a fetal indication is legally prohibited in the country. A retrospective audit of the cytogenetic reports of 1,554 consecutive children with suspected chromosomal disorders who underwent karyotyping at the two main genetic diagnostic centers (HGU and ACGRM) from January 2006 to December 2011 showed that abnormal karyotypes were found in 783 (50.6%) children (Thillainathan, Sirisena, Kariyawasam, Jayasekara, & Dissanayake, ). Numerical and structural abnormalities accounted for 90.8% and 9.2%, respectively.…”
Section: Introductionmentioning
confidence: 99%